Pengembangan Model Supervisi Kolegial Berbasis MGMP Untuk Meningkatkan Mutu Pembelajaran Guru - Maria Silaen; Syawal Gultom; Aman Simare-mare (Universitas Negeri Malang, 2026)
Abstract: This study aims to develop a collegial supervision model based on the Subject Teacher Forum (MGMP) to improve the quality of teacher learning, particularly in the aspects of planning, implementation, and assessment of learning. This study uses a Research and Development (R&D) approach adapted from the Borg and Gall model. This study was conducted at SMA Negeri 4 Medan. The sample selection of this study used a purposive sampling technique, making 25 teachers as respondents and involving the principal, vice principal for curriculum, and the head of MGMP to obtain data on the implementation of academic supervision in schools. Data collection techniques for this study were observation, interviews, questionnaires, and documentation. The research instruments used were the teacher learning quality instrument, the collegial supervision instrument, and the instrument for assessing the feasibility of the model by experts. Data analysis techniques used descriptive qualitative and quantitative analysis. Qualitative analysis was used to describe the conditions of the implementation of academic supervision in schools. Quantitative analysis was used to analyze the data from the questionnaire on the quality of teacher learning and the feasibility of the developed supervision model. The results showed that the quality of teacher learning increased in all aspects, with an N-Gain value of 0.68 (moderate) for planning and implementation, and 0.70 (high) for assessment. The paired sample t-test results showed a significant difference between pretest and posttest scores (p < 0.001), confirming the effectiveness of the developed model. This model can be applied in secondary education and teacher professional development programs, particularly in MGMP as a professional learning community, to support collaborative supervision and improve teaching quality. The uniqueness of this study lies in the integration of collegial supervision with MGMP, shifting supervision from a top-down approach to a collaborative and reflective process that supports continuous teacher professional development.. Keywords: Collegial Supervision, MGMP, Learning Quality,Teacher Development, Academic Supervision Abstrak: Penelitian ini bertujuan untuk mengembangkan model supervisi kolegial berbasis Forum Guru Mata Pelajaran (MGMP) untuk meningkatkan kualitas pembelajaran guru, khususnya pada aspek perencanaan, pelaksanaan, dan penilaian pembelajaran. Penelitian ini menggunakan pendekatan Research dan Development (R&D) yang diadaptasi dari model Borg dan Gall. Penelitian ini dilaksanakan di SMA Negeri 4 Medan. Pemilihan sampel penelitian ini menggunakan teknik purposive sampling menjadikan 25 guru sebagai responden dan melibatkan kepala sekolah, wakil kepala sekolah bidang kurikulum, serta ketua MGMP untuk memperoleh data mengenai pelaksanaan supervisi akademik di sekolah. Teknik pengumpulan data penelitian ini yaitu observasi, wawancara, angket, dan dokumentasi. Instrumen penelitian yang digunakan yaitu instrumen mutu pembelajaran guru, instrumen supervisi kolegial, serta instrumen penilaian kelayakan model oleh ahli. Teknik analisis data menggunakan analisis deskriptif kualitatif dan kuantitatif. Analisis kualitatif digunakan untuk menggambarkan kondisi pelaksanaan supervisi akademik di sekolah. Analisis kuantitatif digunakan untuk menganalisis data hasil angket mutu pembelajaran guru serta kelayakan model supervisi yang dikembangkan. Hasil penelitian menunjukkan bahwa kualitas pembelajaran guru meningkat pada semua aspek, dengan nilai N-Gain sebesar 0,68 (sedang) untuk perencanaan dan pelaksanaan, dan 0,70 (tinggi) untuk penilaian. Hasil uji t sampel berpasangan menunjukkan perbedaan signifikan antara skor pretest dan posttest (p < 0,001), yang menegaskan efektivitas model yang dikembangkan. Model ini dapat diterapkan dalam pendidikan menengah dan program pengembangan profesional guru, khususnya dalam MGMP sebagai komunitas pembelajaran profesional, untuk mendukung supervisi kolaboratif dan meningkatkan kualitas pengajaran. Keunikan studi ini terletak pada integrasi supervisi kolegial dengan MGMP, menggeser supervisi dari pendekatan top-down ke proses kolaboratif dan reflektif yang mendukung pengembangan profesional guru secara berkelanjutan. Kata kunci: Supervisi kolegial, MGMP, Kualitas Pembelajaran, Pengembangan Guru, Supervisi Akademik